Céréales, pains, levains et fours dans la région d'El Hoceima - Dominique Caubet; Yildiz Aumeeruddy-Thomas (Revue d'ethnoécologie)
The preparation of flours and breads from cereals is a key activity in the Mediterranean region, the area fo origin of the domestication of wheat, barley, small spelled, rye and oats. Cereals have been used in the form of semolina, pasta, flour, leavened and unleavened breads, since ancient times. Our cross-disciplinary ethnobotanical and linguistic approach focuses on discourses and terms that seek to better understand the uses of different forms of speech and to convey what the social groups under study attribute to prepared foods and to the nature of the plants that make them up. These ethnobotanical and linguistic studies in the Rif open the way to better understanding this knowledge, through the expression of language and the nature of exchanges between communities speaking different dialects.The Rif is an ideal situation for both linguists and ethnobotanists to study exchange situations, language contacts and food techniques, on the borders between Arabic-speaking and Berber-speaking groups.On the ethnobotanical level, this work allowed us to identify the operating chains of cereal processing into flour, bread and cooking methods, including a very rich lexicon explaining the importance of these products for the inhabitants of the two villages studied. We discuss this set of techniques and the uses of cereal products and leaven, the way they are inserted in the surrounding cereal fields and almond orchards, and in the domestic unit. These data are novel to this day for this part of the Rif.